Investigating the evolution of water-soluble organic carbon in evaporating cloud water. Issue 1 (22nd December 2020) - Pratap, Vikram; Christiansen, Amy E.; Carlton, Annmarie G.; Lance, Sara; Casson, Paul; Dukett, Jed; Hassan, Hesham; Schwab, James J.; Hennigan, Christopher J.
Abstract : Cloud cycling plays a key role in the evolution of atmospheric particles and gases, producing secondary aerosol mass and transforming the optical properties and impacts of aerosols globally. Abstract : Cloud cycling plays a key role in the evolution of atmospheric particles and gases, producing secondary aerosol mass and transforming the optical properties and impacts of aerosols globally. In this study, bulk cloud water samples collected at Whiteface Mountain (Wilmington, NY) in the summer of 2017 were aerosolized, dried to 50% RH, and analyzed for the evaporative loss of water soluble organic carbon (WSOC) and for brown carbon (BrC) formation. Systematic WSOC evaporation occurred in all cloud water samples, while no evidence for drying induced BrC formation was observed. On average, 11% (±3%) of WSOC evaporated when the aerosolized cloud droplets were dried to 50% RH, though this represents a lower bound on the WSOC reversibly partitioned to clouds due to experimental constraints. To our knowledge, this represents the first direct measurements of organic evaporation from actual cloud water undergoing drying. Formate and acetate contributed 19%, on average, to the evaporated WSOC, while no oxalate evaporation occurred. GECKO-A model simulations were carried out to predict the production of WSOC compounds that reversibly partition to cloud water from photooxidation of an array of VOCs. The model results suggest that precursor VOC identity and oxidation regime (VOC:NO x ) have a dramatic effect on the reversible partitioning of WSOC to cloud water and the abundance of aqSOA precursors, though the higher abundance of reversibly partitioned WSOC predicted by the model may be due to aqueous production of low-volatility material in the actual cloud samples. This study underscores the importance of the large fraction of unidentified compounds that contribute to WSOC in cloud water and their aqueous processing.